(untitled) (Global Journal of Human-Social Science, 2014)
Are different government plans to cut the rate of young people known as NEET, now in the age between 15 and 29 years. These people have a serious problem to do a life plan and emancipation, however, has a much greater technological power than their parents and live in a continuously changing world. With the rise of massive open online courses (MOOC), these people have an opportunity to improve their quality of life in this model of education. However, it is possible that they might have troubles to adapt to this new way of learning. This research takes two courses with more than 6,500 students each, where most of the students are NEET. One of the courses is about something completely technology (video games) and the other is more traditional (law). The experiment will try to answer the question of whether the technological novelty of the subject influences in their interest and if it influences the occupational wishes of NEET.